[Beethoven life mask with laurel wreaths.] - Russia?. : s.n. (2026)
1 postcard : black & white ; 9 x 13.5 cm. (3.5 x 5.5 in.). Addressed and inscribed on verso in Russian. Postmarked 1909. Superimposed on score of the pathètique Sonata, first movement.